Primary Extra Nodal Lymphoma: A Single-Centre Experience from Nepal - Jha, Ajaya Kumar; Shrestha, Prakash; Subedi, Garima; Sinha, Arvind Kumar (Journal of Nobel Medical College, 2026)
Background: Non-Hodgkin’s lymphomas comprise a diverse group of lymphoid malignancies with increasing global incidence. Primary extra nodal lymphoma, defined by initial involvement of non-nodal tissues, represents a distinct clinicopathological entity. Evidence from low- and middle-income countries, including Nepal, remains limited. To describe the demographic characteristics, anatomical distribution, histological subtypes, and treatment patterns of patients diagnosed with primary extra nodal lymphoma at a tertiary care center in Nepal.Materials and Methods: A retrospective observational study was conducted including patients diagnosed with primary extra nodal lymphoma between January 2022 and June 2025. Diagnosis was established through histopathological examination and immunohistochemistry. Demographic, clinical, pathological, and treatment-related data were analyzed using descriptive statistics.Results: A total of 36 patients were included. The mean age at diagnosis was 42.2 years (range: 10–82 years), with a median age of 45 years. Males accounted for 58% of cases. B-cell lymphomas constituted 92% of cases, with diffuse large B-cell lymphoma being the most frequent subtype. The gastrointestinal tract was the most commonly involved site, followed by the head and neck region. CHOP-based chemotherapy regimens formed the backbone of treatment in the majority of patients.Conclusion: Primary extra nodal lymphoma in this cohort demonstrated a predominance of gastrointestinal involvement and B-cell histology, particularly diffuse large B-cell lymphoma. The gastrointestinal tract was the most commonly involved site, followed by the head and neck region. CHOP-based chemotherapy regimens formed the backbone of treatment in the majority of patients